The Potent Novel CDK4/6 Inhibitor TQB3616 in Hormone Receptor Positive Breast Cancer: Preclinical Characterization with in vitro and Human Tumor Xenograft Models - Hu W; Wang L; Luo J; Zhang J; Li N (Breast Cancer: Targets and Therapy, 2023)
Wenyu Hu,1,* Lei Wang,1,* JiaLing Luo,1 Jian Zhang,2 Nanlin Li1 1Department of Thyroid, Breast and Vascular Surgery, Xijing Hospital, Air Force Military Medical University, Xi’an, Shaanxi, People’s Republic of China; 2The State Key Laboratory of Cancer Biology, Department of Biochemistry and Molecular Biology, Air Force Military Medical University, Xi’an, Shaanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nanlin Li; Jian Zhang, Email nanlin-74@163.com; biozhangj@fmmu.edu.cnPurpose: Inhibition of the cyclin-dependent kinase (CDK) 4/6-retinoblastoma (RB) pathway exerts a considerable inhibitory effect, preventing the spread and metastasis of breast cancer cells and promoting tumor regression. In this study, we examined the antitumor activity of TQB3616, a novel inhibitor of CDK4/6 activity, which showed a greater efficacy improvement in antitumor effects.Methods: TQB3616 group, abemaciclib group and endocrine or HER-2 targeted combination therapy group were set up respectively. The effects of drugs on cell proliferation activity, cell cycle, apoptosis, downstream protein expression and gene expression of HR positive (T47D, MCF-7) and HER-2 positive (BT474, MDA-MB-361) breast cancer cell lines were studied. The antiproliferative effect of TQB3616 was also measured in vivo.Results: TQB3616 showed a remarkable inhibitory effect on the proliferation of hormone receptor-positive breast cancer cells in vitro. In addition, TQB3616 combined with endocrine therapy or Human Epidermal Growth Factor Receptor 2 (HER2) targeted therapy showed significant synergistic antitumor activity in estrogen receptor (ER)-positive/HER2-negative or HER2-positive breast cancer. In contrast to abemaciclib, which targets the CDK4/6 pathway with proven efficacy, the oral agent TQB3616 not only induced G1 stalling, leading to a profound reduction in the level of RB protein phosphorylated at Ser807/811, but also showed enhanced tumor killing effects by promoting cell apoptosis. Oral administration of TQB3616 showed more potent antitumor activity than abemaciclib in an in vitro breast cancer xenograft model, causing significant tumor regression associated with sustained target inhibition in tumor tissue and manageable in vivo toxicity.Conclusion: The results of this study indicate that TQB3616 is a novel CDK4/6 inhibitor, and its highly effective antitumor activity against breast cancer is expected to yield promising therapeutic effects in clinical studies.Keywords: breast cancer, endocrine therapy, CDK inhibitors, apoptosis, abemaciclib